MORPHO-STRUCTURAL AND PHOTOCATALYTIC PROPERTIES OF SnO₂ NANOPARTICLES - ŞTEFAN, Maria; PANA, Ovidiu; LEOŞTEAN, Cristian; POPA, Adriana; TOLOMAN, Dana; MACAVEI, Sergiu; LAZĂR, Diana; BARBU-TUDORAN, Lucian (Studia Universitatis Babeș-Bolyai Chemia, 2019)
SnO2 nanoparticles were successfully synthesized by precipitation method, in the presence of hexadecyltrimethyl ammonium bromide (CTAB) and polyethylene glycol 600 (PEG 600) as surfactants. The obtained SnO2 nanoparticles were characterized by X-ray diffraction (XRD), porosity and surface area measurements (BET), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS). Also, photocatalytic properties toward degradation of Rhodamine B (RhB) were investigated. It was found that morpho-structural properties are influenced by the preparative conditions of doped SnO2 nanoparticles.